Supporting Staffs’ Understanding on Merdeka Belajar Kampus Merdeka: A Case Study in Universitas Islam Malang - Dwi Fita Heriyawati; Ifit Novita Sari; Noni Mia Rahmawati; Sonny Elfiyanto (Universitas Negeri Malang, 2023)
Abstract: The study is conducted to find out the understanding of the supporting staffs in Universitas Islam Malang on Merdeka Belajar Kampus Merdeka (MBKM) policy. The MBKM policy is related to giving the students flexibility in learning to enable them acquire more expertise in different departments or universities. As a part of the university stakeholders, the supporting staffs need to have complete understanding on the policy to support the implementation of the policy in Universitas Islam Malang. The study is a case study that employed mixed method approach by using surveys and interviews as the instruments. Form the collected data, it can be concluded that the supporting staffs in Universitas Islam Malang have known the policy, but have not completely understood all of the substances yet. Some of the substances that have not been understood are related to the semesters allowed for the students to learn outside their own departments and the number of credits given to the students as a form of recognition on the competences they earned from joining the MBKM activities. Therefore, more continuous socializations about the policy are still need to be carried out by the university and/or the Ministry of Education, Culture, Research, and Technology of Indonesia. Keywords: supporting staffs; understanding; flexible learning; Merdeka Belajar Kampus Merdeka